Ecological economics for sustainable development - Indian Society for Ecological Economics (Delhi) (Delhi Academic Foundation, 2001)
Indian Society for Ecological Economics brings together the proceeding lead papers and abstracts of contributed papers at the first Biemmial conference of the Indian society for ecological Economics gives a developing country perspective to the issues ref
Keywords: Sustainable development; Economic Development; Environmental aspects